Ordinances of the Town of Jacksonville, at 44-45, Ordinance No. 53, § 9 (1876) - (:unkn) unknown (My University, 1876)
All persons are forbidden to shoot or fire off any gun within said cemetery enclosures, or put or turn loose any animal therein.
Keywords: DISCHARGE